Amplification genetic engineering strategy by Crispr-Cas13 Enzymes for detection and treatment COVID-19 mediated with gold nanoparticle (AUNP) - Salsabila Farah Rafidah; Ilham Rahmanto; Ardellia Bertha Pratiska (Universitas Muhammadiyah Surabaya, 2022)
WHO declared the disease outbreak due to the COVID-19 coronavirus a global pandemic. Indonesian government's efforts to eradicate the pandemic through mass screening have not been effective due to the limitations of the three main modalities used to detect COVID-19, including Rapid Test Diagnostic (RTD) antibodies, RTD antigens, and Reverse Transcriptase-Polymerase Chain Reaction (RT-RTD PCR), In addition, other detection tools are sometimes used, such as Enzyme-Linked Immunosorbent Assay (ELISA) and rapid molecular tests. To eradicate this pandemic, the government needs COVID-19 detection tools that are effective, cheap, fast, and accessible. To determine the application of the genetic engineering strategy of amplification by the CRISPR-cas13 enzyme for detecting and treating COVID-19 mediated by gold nanoparticles (AuNP). This research uses a qualitative literature study with content analysis, observation development, and literature study; an alternative solution to this problem is CRISPR-Cas13, achieved by the SHERLOCK method. This method designs and screens a targeted group of CRISPR RNAs based on the identification of functional crRNAs of SARS-CoV-2. Amplification of CRISPR-Cas13 by SHERLOCK and PAC-MAN enzymes has the potential to be the latest detection and treatment method for gold nanoparticle-mediated COVID-19 (AuNP) in Indonesia.